Veterans Health Administration response to 2021 recall of Philips Respironics devices: A case study - Belkora, Jeffrey K.; Fields, Barry; Shamim-Uzzaman, Q. Afifa; Stratford, Donna; Alfandre, David; Hollingshaus, Scott; Yackel, Edward; Geppert, Cynthia; Nechanicky, Penny; Nichols, Ardene; Williams, Katherine; Reichert, Jill; et al. (Frontiers in Sleep, 2023)
This case study describes, for the time frame of June 2021 through August 2022, the U.S. Veterans Health Administration (VHA) organizational response to a manufacturer’s recall of positive airway pressure devices used in the treatment of sleep disordered breathing. VHA estimated it could take over a year for Veterans to receive replacement devices. Veterans awaiting a replacement faced a dilemma. They could continue using the recalled devices and bear the product safety risks that led to the recall, or they could stop using them and bear the risks of untreated sleep disordered breathing. Using a program monitoring approach,, we report on the processes VHA put in place to respond to the recall. Specifically, we report on the strategic, service, and operational plans associated with VHA’s response to the recall for Veterans needing replacement devices. VHA’s strategic plan featured a clinician-led, as opposed to primarily legal or administrative response to the recall. The recall response team also engaged with VHA’s medical ethics service to articulate an ethical framework guiding the allocation of replacement devices under conditions of scarcity. This framework proposed allocating scarce devices to Veterans according to their clinical need. The service plan invited Veterans to schedule visits with sleep providers who could assess their clinical need and counsel them accordingly. The operational plan distributed devices according to clinical need as they became available. Monitoring our program processes in real time helped VHA launch and adapt its response to a recall affecting more than 700,000 Veterans.